Тенденції розвитку та напрямки реновації сільських поселень України - Сільник, Олександра; Silnik, Oleksandra (Видавництво Львівської політехніки, 2020)
У представленій статті висвітлено основні напрямки розвитку українських сільських поселень протягом ХХ ст., культурно-побутову інфраструктуру та архітектурно-планувальні вирішення поселень. Висвітлено проблеми й напрямки їх вирішення у сучасному розвитку сільських населених пунктів України.

The rural settlement occupies a very important place in the modern socio-cultural structure of our state. Ukraine has a huge agricultural potential, and rural development has a significant impact on the economic situation. An important task of society is to increase the quality of life of its inhabitants. The comfort of rural settlements is influenced by the quality of housing, the level of cultural and industrial infrastructure. Domestic and foreign experience confirms the importance of the development of rural entrepreneurship, services, cultural education. The issue of solving the construction and planning of a modern village can be solved taking into account detailed analysis of the existing state of the territory. All components of settlements, from the condition of streets and existing utilities to existing buildings, are integral parts. If we cover the issues of the street network, the quality does not meet the modern requirements for the operation of modern equipment. The disadvantages are both in the quality of the street pavement and in the peculiarities of the layout, this applies to unregulated street profiles, unsuccessful junctions of nodal elements. Construction and development of public buildings in modern villages of Ukraine also do not meet the needs of modern residents of settlements. A number of reforms already underway by the state prove that rural settlements need to be renewed not only in the field of the technological equipment but also in the structure of construction in general. One of the methods of solving this problem is the arrangement of cultural and domestic, administrative, educational institutions in rural areas, landscaping for active and quiet recreation. At the present stage, there are also problems with solving the development of settlements, which are under the influence of large urban areas. These settlements combine agricultural and industrial areas, perform a wide range of functions that are not always successfully combined, and have a positive impact on the living standards of the peasants themselves. Given the current stages of transformation of settlements in modern conditions, there is a need to create virtual models of development of areas with projected areas of development of both residential areas and areas with industrial and economic purposes. Work on the renovation of existing rural settlements should take into account a wide range of factors: the existing natural and climatic environment, traditions of the local population, existing infrastructure, both cultural and economic, location in the structure of administrative planning, and interaction of adjacent territories, etc.
On the issue of revitalization of public centers in rural settlements of Ukrain
Keywords: село; сельбищні території; архітектурно-планувальна структура; культурно-побутова інфраструктура; сільське поселення; реновація; village; settlements; architectural and planning structure; cultural and household infrastructure; rural settlement; renovation; 711. 364-1(332.5)